2022
DOI: 10.1029/2022ja031042
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Long‐Term Evolution of the Ionosphere During the Holocene

Abstract: To date, no natural media is available to derive the “ancient” ionosphere, so the current understanding of ionospheric long‐term trends mainly comes from analyzing ∼70 yr modern measurements supplemented by theoretical simulations. In this study, for the first time, we expanded the ionosphere simulation to the whole Holocene (9455 BCE to 2015 CE) using the Global Coupled Ionosphere‐Thermosphere‐Electrodynamics Model developed at the Institute of Geology and Geophysics, Chinese Academy of Sciences, driven by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
(172 reference statements)
0
4
0
Order By: Relevance
“…(2023) and Yue et al. (2022) found that a larger vertical drift in the equatorial region because of decreased geomagnetic fields will result in less electron density around the equator and more in the EIA region which would explain the low latitude electron density changes in Figure 6. Zhang et al.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…(2023) and Yue et al. (2022) found that a larger vertical drift in the equatorial region because of decreased geomagnetic fields will result in less electron density around the equator and more in the EIA region which would explain the low latitude electron density changes in Figure 6. Zhang et al.…”
Section: Discussionmentioning
confidence: 88%
“…A closer look at Figures 6d and 6h leads us to conclude that this is reasonable since there are latitudes where the electron column density increases in the period leading up to 1950. Zhou et al (2023) and Yue et al (2022) found that a larger vertical drift in the equatorial region because of decreased geomagnetic fields will result in less electron density around the equator and more in the EIA region which would explain the low latitude electron density changes in Figure 6. Zhang et al (2011) analyzed nearly four decades of incoherent scatter radar observations and found at noontime a change in electron density of +0.45%/decade at 150 km and between −0.05% and −0.35%/decade at higher altitudes.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations